Does consumer customization strategy always benefit the platform firm's profit?. Issue 5 (11th November 2019) - Wang, Can-you; Li, Cheng-long; Su, Qin
Abstract : Purpose: The purpose of this paper is to study the price decisions and profits of two firms in a competitive market in which one platform firm considers whether to adopt a consumer customization strategy. Design/methodology/approach: This study develops the consumer's utility function, which captures consumers' behavioural and emotional factors in the self-customizing process, and it adopts a game theory approach to analyze the equilibrium price and equilibrium profit for each firm. Findings: The results show that increased sensitivity in consumer customization might not benefit the platform, especially when the size of the consumer group deriving positive additional utility from the self-customizing process is small. Interestingly, if the consumer customization sensitivity is high, increasing sensitivity can benefit both firms by relaxing competition between them, while it can hurt consumer surplus. The study also further identifies the conditions under which platforms can adopt a consumer customization strategy. Research limitations/implications: Two major limitations of the study are that the model does not involve price discrimination or explore the value of adopting a consumer customization strategy in a vertically differentiated market. Practical implications: This study offers managerial insights for the platforms that intend to invest in a consumer customization strategy, including providing a more simple, more efficient self-customizing process for consumers; empowering consumers to broadcast their creations to a large network by social media technologies; addressing how to determine what consumers really need and want; and so on. Originality/value: Little research has been performed to analyze the impacts of adopting a consumer customization strategy on pricing decisions in a duopoly market by capturing consumers' behavioural and emotional factors. While this study explores the above research issue, it also illustrates the effect of the adoption of a consumer customization strategy from a consumer surplus perspective.